Characterizing Repeats in Two Whole-Genome Amplification Methods in the Reniform Nematode Genome - Nyaku, S.T.; Sripathi, V.R.; Lawrence, K.; Sharma, G. (Hindawi, 2021)
One of the major problems in the U.S. and global cotton production is the damage caused by the reniform nematode, Rotylenchulus reniformis. Amplification of DNA from single nematodes for further molecular analysis can be challenging sometimes. In this research, two whole-genome amplification (WGA) methods were evaluated for their efficiencies in DNA amplification from a single reniform nematode. The WGA was carried out using both REPLI-g Mini and Midi kits, and the GenomePlex single cell whole-genome amplification kit. Sequence analysis produced 4 Mb and 12 Mb of genomic sequences for the reniform nematode using REPLI-g and SIGMA libraries. These sequences were assembled into 28,784 and 24,508 contigs, respectively, for REPLI-g and SIGMA libraries. The highest repeats in both libraries were of low complexity, and the lowest for the REPLI-g library were for satellites and for the SIGMA library, RTE/BOV-B. The same kind of repeats were observed for both libraries; however, the SIGMA library had four other repeat elements (Penelope (long interspersed nucleotide element (LINE)), RTE/BOV-B (LINE), PiggyBac, and Mirage/P-element/Transib), which were not seen in the REPLI-g library. DNA transposons were also found in both libraries. Both reniform nematode 18S rRNA variants (RN_VAR1 and RN_VAR2) could easily be identified in both libraries. This research has therefore demonstrated the ability of using both WGA methods, in amplification of gDNA isolated from single reniform nematodes.
Research Article